Multiobjective evolutionary programming based for network reconfiguration in a distribution system / Marleyana Md. Jude - Md. Jude, Marleyana (2005)
This project report presents an Evolutionary Programming optimization technique for optimal reconfiguration of radial distribution network for loss minimization and voltage improvement in the system. Evolutionary programming is used to determine the best tie-line and sectionalizing switch combination, minimum losses and voltage improvement in the system. The proposed method has been tested on standard IEEE 33 bus distribution system. The results have been compared with initial network. From the result, the developed technique is able to identify the best tie-line and sectionalizing switch pair that with minimize the total losses in the system and also improve the voltage for locating the tie switches and providing the minimum number of sectionalizing switches in the branches.